2017
DOI: 10.1080/21645515.2017.1264784
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization rates for intussusception in children aged 0–59 months from 2009 to 2014 in Italy

Abstract: The real cause of intussusception is not fully understood and a variety of conditions have been associated with it (Meckel diverticulum, polyps, duplication cysts, parasites, Henoch-Schönlein purpura, cystic fibrosis, hemolytic-uremic syndrome and infectious gastroenteritis). Furthermore few European countries, following WHO recommendation to monitor baseline incidence of intussusception before implementation of immunization program for rotavirus, used intussusception rate as a baseline value to compare the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…A prospective case-control study showed that experiencing gastroenteritis during the 30 days before an IS diagnosis was associated with IS in children aged 0-59 months (odds ratio: 11.6; 95% CI: 3.2-41.2; p-value<0.001) (20). Although other risk factors for gastroenteritis were not explored in that study, results are consistent with other studies that identified bacterial and viral gastroenteritis as major risk factors for developing IS (21)(22)(23)(24)(25). While adenovirus is the primary causative agent frequently detected in IS cases, some studies demonstrated an association with rotavirus (8-10).…”
Section: Ge and Is But Not Between Fracture And Issupporting
confidence: 88%
“…A prospective case-control study showed that experiencing gastroenteritis during the 30 days before an IS diagnosis was associated with IS in children aged 0-59 months (odds ratio: 11.6; 95% CI: 3.2-41.2; p-value<0.001) (20). Although other risk factors for gastroenteritis were not explored in that study, results are consistent with other studies that identified bacterial and viral gastroenteritis as major risk factors for developing IS (21)(22)(23)(24)(25). While adenovirus is the primary causative agent frequently detected in IS cases, some studies demonstrated an association with rotavirus (8-10).…”
Section: Ge and Is But Not Between Fracture And Issupporting
confidence: 88%
“…20 , 21 Moreover, Italian data on intussusception in the absence of RV vaccination, as well as a study conducted in Sicily before RV vaccination was introduced, showed a similar increasing trend in intussusception among children aged 12–59 months, indicating a role of other risk factors for intussusception. 22-26 …”
Section: Discussionmentioning
confidence: 99%
“…34 The estimate of the health and economic burden of RVGE emergency room and outpatient visits adopted in this work was performed using methodology of a multicenter study conducted in seven European countries, including Italy (Padua). 22 …”
Section: Discussionmentioning
confidence: 99%
“…5,59 The risk of intussusception remained highest in children <1 year, however, there was a significant increasing trend of intussusception hospitalizations in some older age groups (1-2 years and 2-6 years) between 2005 and 2014, 57 with another study reporting increasing incidence rates of 18% overall and 40% in ages 1-5 years. 58 From the national hospital discharge database, overall incidence in children <16 years of age, however, was stable from 2005 to 2012. 60 The reported increased post-vaccination risk is low, at around 1-6 additional cases per 100,000, and occurs mostly within 7 days of the first dose.…”
Section: Safetymentioning
confidence: 99%